Students’ Perceptions of Duolingo as Interactive English Learning Media - Fitra A. Jaelani; Karmila Machmud; Yunita Hatibie (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study explored junior high school students’ perceptions of Duolingo as an interactive English learning medium at SMP Negeri 4 Limboto Barat. The study employed a qualitative descriptive approach to examine students’ learning experiences in using Duolingo during English learning activities. The data were collected through semi-structured interviews involving 22 learners and were analyzed using thematic analysis by referring to Bimo Walgito’s (2010) perception theory and Self-Determination Theory proposed by Ryan and Deci (2000). While previous studies often focus on isolated aspects of digital learning, this study explores students’ experiences through five interconnected perceptual dimensions derived from Walgito’s perception theory. The findings revealed that students generally had positive perceptions toward the use of Duolingo in English learning, yielding three major themes: Students’ Perceptions of Motivation and Engagement, Perceived Support for English Learning, and Learning Experiences and Practical Challenges. The application increased students’ interest, supported vocabulary development, and provided immediate feedback that boosted classroom confidence. However, several technical challenges, such as unstable internet connections and limited device capabilities, were found to affect the learning process. The study concludes that Duolingo functions as an effective interactive English learning medium that promotes meaningful learning experiences. Practically, these findings can inform English teachers on how to strategically integrate gamified tools as classroom complements while mitigating technical barriers.